The Book and its Industry, the State of Play through Analysis of its Bibliographic Production (1958-2021): Perspectives and Tools for Mesoanalytical and Mesoeconomic Research - Vázquez Álvarez, Iñaki (Revista General de Información y Documentación, 2021)
Based on the hypothesis that there is no strictly mesoanalytical and mesoeconomic research on the book and its industry, this article systematises the most relevant academic and professional bibliographic production (1958-2021) relating to the two objects of study, organising it into six analytical perspectives – four consolidated and two propositional. It then organises the stated production within each of these perspectives, to subsequently identify their most significant contributions for future mesoanalytical and mesoeconomic research. Finally, the article validates the hypothesis put forth.
Keywords: book; book industry; Cultural Industries; History of Books and of Reading; Sociology of Books and of Publishing; Economy of Culture; Political Economy of Communication and Culture; Industrial economics; Mesoeconomics; Mesoanalysis